Marketing, Operations, And Human Capital Strategy Implementation for Startup Business: Bilik Hukum - Gusriantho Mendrofa; Inne Leomora Agnes Sinaga; Rhian Indradewa; Semerdanta Pusaka; Agus Munandar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to (1) determine the marketing planning of the Bilik Hukum in achieving the long-term strategy, (2) find out the operational planning of the Bilik Hukum in achieving the long-term strategy, and (3) determine the strategy in achieving 100% of the strength of human capital of Bilik Hukum. In this study using SWOT analysis in determining planning in overcoming the overall challenges. The results of this study indicate that Bilik Hukum develops competitive advantage through Segmenting, Targeting, and Positioning (STP) and marketing mix strategies to create business continuity and competitive advantage. From an operational perspective, Bilik Hukum differentiates its products, competitive prices, and be responsive in providing services. To achieve 100% HR strength as a long-term strategy, the aspects that need to be considered are (1) the projection of the number of employees needed, (2) identifying HR in the organization, (3) analyzing the balance of demand and supply, and (4) run the action program. The results of this study are expected to assist new businesses in determining their plans so that they have superior, competitive, and profitable capacities in achieving long-term strategies.